Anti-ultraviolet properties of β-cyclodextrin-grafted cotton fabrics dyed by broadleaf holly leaf extract. Issue 21 (November 2020) - Liu, Jinshu; Ma, Xiaoyan; Shi, Wenzhao; Xing, Jianwei; Ma, Chaoqun; Li, Susong; Huang, Yayi
The aim of the study was to investigate the anti-ultraviolet properties of β-cyclodextrin-grafted cotton fabrics dyed with broadleaf holly leaf extract. Flavonoids were extracted from broadleaf holly leaf by maceration and a stoichiometry of 1:1 inclusion complex with β-cyclodextrin was formed. Characterized by the fluorescence spectrum and ultraviolet spectrophotometry, the fluorescence intensities and ultraviolet absorption of the macerated extract were enhanced by increasing the amount of cyclodextrin. Cotton fabrics were grafted with β-cyclodextrin through a crosslinking reaction based on citric acid in the presence of sodium hypophosphite then dyed with the macerated extract of broadleaf holly leaf used as a natural ultraviolet absorbent. The anti-ultraviolet property of fabrics dyed by a macerated extract was characterized in terms of the ultraviolet protection factor. It was noted that the cotton fabrics grafted with β-cyclodextrin exhibit enhanced anti-ultraviolet and wrinkle recovery properties compared to the unmodified samples and show an excellent durability against 30 washing cycles, accompanied by a loss of tensile strength.